PENGARUH KINERJA KEUANGAN TERHADAP KONDISI FINANCIAL DISTRESS (STUDI EMPIRIS PADA PERUSAHAAN PERDAGANGAN ECERAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - admin, TRESNA VIKA RATNASARI B1021131015 (Jurnal Manajemen Update, 2017)
Financial distress condition begins from difficulty of liquidity (short period) as a the lowest financial distress indication until the the highest bankcruptcyThe purpose of this research was to describe the influence of leverage ratio, liquidity ratio, profitability ratio and activity ratio in retail trading companies that registered in BEI where in this research used financial report by observing period for six years which was 2011 to 2016. Financial distress predictor by using modification Z-Score as an activity measurement on the retail trading companies was registered in BEI. In this research verified the correlation of regressiion between dependent variabel and independent variabel with panel data,regression analyzing of panel data used three estimation model tehniques were common effect model, fixed effect model and random effect model. In this research showed that partial test result from leverage ratio, liquidity ratio,and profitabilitas had the influence significantly toward financial distress Keywords : Financial Distress, Z-score, leverage ratio, liquidity ratio,  profitability ratio and activity ratio